Fat-free noncontrast whole-heart cardiovascular magnetic resonance imaging with fast and power-optimized off-resonant water-excitation pulses - Mackowiak, Adèle L.C.; Piccini, Davide; van Heeswijk, Ruud B.; Hullin, Roger; Gräni, Christoph; Bastiaansen, Jessica A.M. (Journal of cardiovascular magnetic resonance, 2024)
Cardiovascular magnetic resonance imaging (CMR) faces challenges due to the interference of bright fat signals in visualizing structures, such as coronary arteries. Effective fat suppression is crucial, especially when using whole-heart CMR techniques. Conventional methods often fall short due to rapid fat signal recovery, leading to residual fat content hindering visualization. Water-selective off-resonant radiofrequency (RF) pulses have been proposed but come with tradeoffs between pulse duration, which increases scan time, and increased RF energy deposit, which limits their applicability due to specific absorption rate (SAR) constraints. The study introduces a lipid-insensitive binomial off-resonant (LIBOR) RF pulse, which addresses concerns about SAR and scan time, and aims to provide a comprehensive quantitative comparison with published off-resonant RF pulses for CMR at 3T. A short (1 ms) LIBOR pulse, with reduced RF power requirements, was developed and implemented in a free-breathing respiratory-self-navigated three-dimensional radial whole-heart CMR sequence at 3T. A binomial off-resonant rectangular (BORR) pulse with matched duration, as well as previously published lipid-insensitive binomial off-resonant excitation (LIBRE) pulses (1 and 2.2 ms), were implemented and optimized for fat suppression in numerical simulations and validated in volunteers (n = 3). Whole-heart CMR was performed in volunteers (n = 10) with all four pulses. The signal-to-noise ratio (SNR) of ventricular blood, skeletal muscle, myocardium, and subcutaneous fat and the coronary vessel detection rates and sharpness were compared. Experimental results validated numerical findings and near-homogeneous fat suppression was achieved with all four pulses. Comparing the short RF pulses (1 ms), LIBOR reduced the RF power nearly two-fold compared with LIBRE, and three-fold compared with BORR, and LIBOR significantly decreased overall fat SNR from cardiac scans, compared to LIBRE and BORR. The reduction in RF pulse duration (from 2.2 to 1 ms) shortened the whole-heart acquisition from 8.5 to 7 min. No significant differences in coronary arteries detection and sharpness were found when comparing all four pulses. LIBOR pulses enabled whole-heart CMR under 7 min at 3T, with large volume fat signal suppression, while reducing RF power compared with LIBRE and BORR pulses. LIBOR is an excellent candidate to address SAR problems encountered in CMR sequences where fat suppression remains challenging and short RF pulses are required. [Display omitted]